Isolated intracranial hypertension following COVID-19 vaccination: A case report. (9th September 2021) - Thunstedt, Dennis C; Straube, Andreas; Schöberl, Florian
Increased intracranial pressure in cerebral venous sinus thrombosis or metabolic disease has been reported. We present a case of new-onset chronic headache and bilateral papilledema in the setting of elevated intracranial pressure in strong temporal association to vaccination against COVID-19 with AstraZeneca. After repeated drainage of cerebrospinal fluid and conservative drug therapy, pathological findings were regredient. Even in absence of typical risk factors, increased intracranial pressure should be considered in case of clinical suspicion after COVID-19 vaccination.